ASPECT AND IT’S FUNCTIONAL CATEGORY - Karimova M.Ya.; Imamov N.P. (Scholar Express Journal, 2022)
The aspect has a three-dimensional dimension, which has a morphological, semantic and syntactic appearance. We have tried to show and analyze them in detail and give the corresponding characteristics of the aspectual system. Aspect in a broad sense is an additional term that characterizes a number of separate categories of language, characterized by partial semantic similarity and defined in terms of grammatization and lexicalization of certain features.
Keywords: acquisition process; syntactic appearance; grammaticalisation; lexicalisation